Non-homogeneous distribution of steroids in fecal pellets: An example in brown brocket deer (Mazama gouazoubira) with progesterone metabolites - Tanaka, Yuki [UNESP]; Sandoval, Eluzai Dinai Pinto [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Elsevier, 2019)
Measuring reproductive hormones in feces has become an important tool in the endocrine characterization of wild animals’ reproduction. However, several factors may influence its success, such as fecal collection and storage techniques, knowledge of steroid hormone metabolism, the extraction procedure, immunoassay selection, inherent factors, and the distribution of steroid hormones in the feces. It is known that the distribution of these hormones in the feces is not homogeneous, and prior to the extraction of the steroidal metabolites, homogenization of the feces is recommended. Hormonal analysis is based on only a small fraction of the feces, which in theory should be representative of the total. In the case of cervids and other ruminants, feces consist of pellets. Here, the concentration of the steroid metabolites of each pellet was measured in order to evaluate the distribution of the fecal progesterone metabolites concentration in 10 pellets/fecal mass from five female Mazama gouazoubira. There were large variations in fecal progesterone metabolites concentrations between the pellets of the same feces/female, showing the following amplitude variations: Animal A: 112%; Animal B: 164%; Animal C: 115%; Animal D: 62%; Animal E: 108%. These results show the importance of adequate homogenization prior to steroid metabolite extraction.
Keywords: Fecal mass; Non-invasive endocrinology; Reproductive hormone; Wild ruminant